Tindak Pidana Persetubuhan Terhadap Anak Dalam Bentuk Gabungan Tindak Pidana (Studi Putusan Nomor 130/PID.SUS/2021/PN.KPG): The Criminal Act Of Sexual Intercourse Against Children As Combined Criminal Offense: Study Of Decision No. 130/Pid.Sus/2021/Pn.Kpg. - Jonathan Ariesto; Azmi Syahputra (Reformasi Hukum Trisakti, 2024)
The crime of sexual intercourse with a minor is a violation of human rights, especially children's rights. In decision Number 130/Pid.Sus/2021/PN.Kpg, the Defendant had sexual intercourse with the victim more than once. The formulation of the problem in this study is whether the actions committed by the Defendant fall within the qualifications of Article 81 paragraph (2) of the Child Protection Law and whether the characteristics of the actions committed by the Defendant meet the elements to be called continuing actions. This study uses a normative research method that is descriptive in nature and uses secondary data. The results of the study and its conclusions are that the actions committed by the Defendant in case Number 130/Pid.Sus/2021/PN.Kpg who had sexual intercourse with the victim by persuading the victim by expressing affection so that the victim would have sexual intercourse have met the qualifications of Article 81 paragraph (2) of the Child Protection Law and meet the characteristics of continuing actions where sexual intercourse is carried out again within a period of time that is not too far away so that the actions committed by the Defendant meet the elements of continuing actions.